2009
DOI: 10.1590/s0103-50532009001000014
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive simultaneous determination of epinephrine and tyrosine using an iron(III) doped zeolite-modified carbon paste electrode

Abstract: Um eletrodo de pasta de carbono modificado com zeólitas e dopado com ferro(III) foi usado como um sensor eletroquímico de alta sensibilidade e seletividade para a determinação simultânea de pequenas quantidades de compostos biologicamente importantes como epinefrina (Ep) e tirosina (Tyr). Os resultados da voltametria de pulso diferencial (DPV) usando este eletrodo modificado mostra duas ondas anódicas bem traçadas para a oxidação da Ep e da Tyr, as quais tornam possíveis a determinação simultanêa destes compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…A biosensor based on hemin immobilized reduced graphene oxide nanosheets on glassy carbon electrode, iron (III) doped zeolite modified carbon paste electrode, amperometric sensor based on tetroxide nanoparticles-graphene nanocomposite film modified glassy carbon electrode, chiral electrochemical sensor modified with cysteic acid and gold nanoparticles decorated graphene oxide glassy carbon electrode [23][24][25][26][27] are employed for the sensitive determination of Tyr. There is a report on the analysis of Tyr using SWCNTs modified glassy carbon electrode (GCE) [28], though the GCE requires pretreatment and Tyr suffers from oxidation overpotential at SWCNTs/GCE apart from it not being applied for real sample analysis directly.…”
Section: Introductionmentioning
confidence: 99%
“…A biosensor based on hemin immobilized reduced graphene oxide nanosheets on glassy carbon electrode, iron (III) doped zeolite modified carbon paste electrode, amperometric sensor based on tetroxide nanoparticles-graphene nanocomposite film modified glassy carbon electrode, chiral electrochemical sensor modified with cysteic acid and gold nanoparticles decorated graphene oxide glassy carbon electrode [23][24][25][26][27] are employed for the sensitive determination of Tyr. There is a report on the analysis of Tyr using SWCNTs modified glassy carbon electrode (GCE) [28], though the GCE requires pretreatment and Tyr suffers from oxidation overpotential at SWCNTs/GCE apart from it not being applied for real sample analysis directly.…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption mechanism is further supported by the observation that cathodic reduction peaks are combination of copper oxide and copper phosphate reported by Somasundrum and co-workers [24]. The fact that tyrosine analytical signal is maximum at a pH of 5.5 rules out ion exchange mechanism (which is expected to give maximum analytical signal at pH 3) invoked by Babaei et al [7] in case of zeolite modified carbon paste electrode.…”
Section: Electrocatalytic Mechanismmentioning
confidence: 54%
“…Balla et al [6] reported electrocatalytic oxidation of catechol in presence of copper ions. Babaei and coworkers [7] proposed an ion exchange mechanism in case of Zeolite modified carbon paste electrode for the simultaneous determination of epinephrine (Ep) and tyrosine (Tyr). Several researchers have reported plausible pathways like proton electron transfer processes for electrochemical oxidation of tyrosine using MWCNT and gold nanoparticle modified GCE respectively [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…According to Table 1, the developed biosensor shows wider linear range than some of them [3, 4, 21, 27, 30, 32-35, 48, 49, 51]. The detection limit of the developed biosensor is also better than some electrodes [27,30,32,33,35,48,49,51,6 Journal of Sensors [52], and 2.9 × 10 −8 M for CPE/MWCNTs [28]. In the present study, obtained estimation limit value is comparable with the findings reported in the relevant literature.…”
Section: Linear Range Of the Cp/mwcnt/tyr/nafion Biosensormentioning
confidence: 92%